2017
DOI: 10.1007/978-981-10-6020-5_14
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Epigenome as a Novel Therapeutic Approach for Breast Cancer

Abstract: Breast cancer is one of complex diseases that are influenced by environment. Various genetic and epigenetic alterations are provoking causes of breast carcinogenesis. Dynamic epigenetic regulation including DNA methylation and histone modification induces dysregulation of genes related to proliferation, apoptosis, and metastasis in breast cancer. DNA methylation is strongly associated with the repression of transcription through adding to the methyl group by DNA methyltransferases (DNMTs), and tumor suppressor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 188 publications
0
4
0
Order By: Relevance
“…Dietary intervention is a promising strategy to reverse dysregulation of epigenetic modifications that are associated with tumorigenesis [21]. The anticancer effect of bioactive compounds such as phytochemicals are mediated by epigenetic regulations such as inhibiting DNA methyltransferases (DNMTs), inhibiting histone deacetylase (HDACs), and modulating microRNA [22].…”
Section: Introductionmentioning
confidence: 99%
“…Dietary intervention is a promising strategy to reverse dysregulation of epigenetic modifications that are associated with tumorigenesis [21]. The anticancer effect of bioactive compounds such as phytochemicals are mediated by epigenetic regulations such as inhibiting DNA methyltransferases (DNMTs), inhibiting histone deacetylase (HDACs), and modulating microRNA [22].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, echocardiographic examinations were performed to determine the effect of AS-IV on cardiac function. FS and EF were significantly lower in MI Runx3 to undergo hypermethylation in the promoter region of breast cancer (Oh et al, 2017). We found that MIRT1 could bind Suz12 protein, enabling Suz12 to recruit DNMT3B in the Runx3 promoter region to promote Runx3 methylation and downregulate Runx3 expression.…”
Section: Discussionmentioning
confidence: 77%
“…Studies have shown that DNA methylation plays a role in certain pathological events including breast carcinoma . In addition, certain tumor suppressors were attenuated because of aberrant promoter DNA methylation in the process of breast carcinoma genesis and progression …”
Section: Introductionmentioning
confidence: 99%
“…10 In addition, certain tumor suppressors were attenuated because of aberrant promoter DNA methylation in the process of breast carcinoma genesis and progression. 11 Sesamol, a naturally occurring phenolic water-soluble compound, is usually extracted from sesame seeds and sesame oil. More importantly, it is one of the most active constituents in sesame oil and thought to be responsible for the therapeutic effects of sesame oil.…”
Section: ■ Introductionmentioning
confidence: 99%